Model for sustainable development : integrating environmental impact assessment and project planning - Noorbakhsh, Farhad (1999)
Highlights some shortcomings of the methodology of environmental impact assessment (EIA) and their practical consequences in developing countries. Proposes a project planning model that takes into account the cumulative impacts and assimilative capacity of the envronment.